Bangladesh, South Asia, and the world - Ahmed, Emajuddin; Abul Kalam (Academic Publishers in association with International Studies Association, Bangladesh, 1992)
Chiefly on South Asian affairs; most papers presented at a seminar organized by the International Studies Association, Bangladesh, in Dhaka on 10 August 1990.